Analysis of Il-10 gene sequence in patients with sinonasal polyposis. (September 2015) - Malagutti, N; Stomeo, F; Pelucchi, S; Ronchin, R; Ceccon, M; Malacrida, G; Ciorba, A; Pastore, A; Borin, M; Rizzo, R
Sinonasal polyposis (SNP) is a chronic inflammatory disease of nasal and paranasal cavities. Human leukocyte antigen-G molecules (HLA-G) are non-classic HLA-I molecules with anti-inflammatory and tolerogenic properties. HLA-G production is mainly induced by interleukin (IL)-10. IL-10 is an anti-inflammatory cytokine that inhibits the production of proinflammatory cytokines and induces HLA-class II down-modulation. Recent studies suggest that HLA-G could play a role in SNP pathogenesis; in SNP patients physiological levels of IL-10 (produced by activated peripheral blood CD14+ monocytes) are not able to induce production of HLA-G. Different mechanisms could justify these findings: genomic or amino-acidic sequence alterations in IL-10 lower IL-10 receptor expression, lower IL-10 receptor affinity, or alterations of the intracellular signal transmission. This study analyzes nucleotidic sequence of IL-10 gene in SNP patients. Sequencing of IL-10 gene shows that the lack of HLA-G production by peripheral blood CD14+ monocytes is not related to alterations in IL-10 gene nucleotidic sequence.